Comparative study on 3D printing of polyamide 12 by selective laser sintering and multi jet fusion - Cai, Chao (2023)
Selective laser sintering (SLS) and Multi Jet Fusion (MJF) are two of the most developed powder bed fusion additive manufacturing techniques for the manufacture of polymeric components. In this work, a systematic benchmark and comparison of polyamide 12 (PA12) parts printed by SLS and MJF was conducted on the physicochemical characterization of raw powder materials (EOS PA2200 and HP 3D HR PA12) and their printed specimens, as well as the mechanical performance and printing characteristics of printed objects. Both designated-supply PA12 powders for each technique possessed almost identical thermal features, phase constitutions, functional groups, and chemical states. The mechanical strength of the MJF-printed specimens was slightly stronger than that of SLS-printed counterparts due to the synergistic effect of an area fusion mode and carbon black additive in the MJF process. The SLS-printed specimens had a better surface finish on the top surface, but the MJF-printed specimens showed much smoother front and side surfaces. Scaled-down merlions were printed by both processes for the printing accuracy assessment. The results show that the SLS-printed merlion presented higher profile deviations than those of the MJF-printed counterpart, especially in areas with sharp contours. These fundamental experimental results can provide a comprehensive understanding of SLS and MJF processes and serve as a valuable guideline for their industrial applications.